Vowel recognition based on frequency ranges determined by bandwidth approach - Paulraj, M. P.; Sazali, Yaacob; Mohd Yusof, S. A. (Institute of Eelectrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org